2021
DOI: 10.1186/s12889-021-11285-8
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on COVID-19 testing policies and practices: a qualitative study with scientific advisors and NHS health care workers in England

Abstract: Background As COVID-19 death rates have risen and health-care systems have experienced increased demand, national testing strategies have come under scrutiny. Utilising qualitative interview data from a larger COVID-19 study, this paper provides insights into influences on and the enactment of national COVID-19 testing strategies for health care workers (HCWs) in English NHS settings during wave one of the COVID-19 pandemic (March–August 2020). Through the findings we aim to inform learning abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…The literature and our analysis suggest that organisations need to select the test they use carefully [ 79 ], and help mitigate staff concerns, uncertainties and anxieties about testing [ 26 , 73 , 102 ]. This can be done by considering current guidance and evidence together with effective communication strategies about uncertainties of the test chosen [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature and our analysis suggest that organisations need to select the test they use carefully [ 79 ], and help mitigate staff concerns, uncertainties and anxieties about testing [ 26 , 73 , 102 ]. This can be done by considering current guidance and evidence together with effective communication strategies about uncertainties of the test chosen [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…To conduct ethical analysis, we reviewed existing theories, principles and frameworks in relevant areas, with attention to the potential ethical challenges relevant to COVID-19 testing programmes and infectious diseases outbreaks (e.g. [ 32 , 54 , 56 , 58 – 62 , 73 ]). We also examined applicable legal and regulatory requirements related to testing and information governance (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…While the economic burden of testing in terms of the potential costs of isolation has been widely discussed [ 74 76 ], neither the social costs of testing, nor the everyday emotional and cognitive ‘work’ of ethical reasoning and decision making are widely acknowledged. This is despite social and ethical issues being at the forefront of the testing experience for members of the public [ 4 , 9 , 42 ]. We therefore argue that the burden of testing needs to be understood as practical, economic and ethical and that navigating the ethics of COVID-19 testing can be considered a hidden form of public health and epidemic response work [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social solidarity and a sense of civic responsibility were identified as important motivators to seek testing. Multiple studies also revealed barriers to testing uptake, including logistical issues [5][6][7][8][9], questions of accessibility [5,6], the physical discomfort associated with collecting a sample [10][11][12][13], economic pressures and anxieties [6,10,14,15], and symptom identification [5,6,[15][16][17][18][19][20]. Lack of trust in government bodies to deliver and manage testing was identified as a key barrier to testing in several studies [18,21], a finding that has been repeated in recent research on the role of governmental and interpersonal trust in vaccine uptake [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of pandemics, rapidly evolving research environments, as well as the at times contentious sociopolitical context in which public health policy decisions must be made, create unique challenges for EIDM processes 5 6. Recent research and discussion specific to COVID-19 pandemic decision-making highlight concerns associated with the timing of response decisions, confusion and missed opportunities regarding levels of government responsible for and involved in decision-making, capacity to respond, communication around COVID-19-related guidance, and the use of discourse among authority figures to justify singular COVID-19 response options without attention to alternative policies 7–10. However, this research has fallen short of exploring specific challenges to EIDM as it relates to assessing, interpreting and translating evidence and advising pandemic decision-making from the perspective of those providing evidence.…”
Section: Introductionmentioning
confidence: 99%